2018
DOI: 10.3892/ol.2018.8032
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin may serve an anticancer role in human osteosarcoma cell line U-2 OS by targeting ITPR1

Abstract: The present study aimed to determine the mechanisms of action of curcumin in osteosarcoma. Human osteosarcoma U-2 OS cells was purchased from the Cell Bank of the Chinese Academy of Sciences. RNA sequencing analysis was performed for 2 curcumin-treated samples and 2 control samples using Illumina deep sequencing technology. The differentially expressed genes were identified using Cufflink software. Enrichment and protein-protein interaction network analyses were performed separately using cluster Profiler pack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…In gastric cancer, curcumin and formononetin posed different mechanisms to enhance Dox cytotoxicity [ 59 , 60 ]. These natural compounds exhibit potentiation for main applications in cancer treatment, and also play a supporting role in Dox regimen to overcome the limitation of Dox usage [ 61 , 62 , 63 , 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…In gastric cancer, curcumin and formononetin posed different mechanisms to enhance Dox cytotoxicity [ 59 , 60 ]. These natural compounds exhibit potentiation for main applications in cancer treatment, and also play a supporting role in Dox regimen to overcome the limitation of Dox usage [ 61 , 62 , 63 , 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…For osteosarcoma, several researchers have successfully proven that curcumin can induce the MG63, U2OS, and HOS cell line apoptosis based on different signal pathways (32,33,(47)(48)(49)(50). Besides, curcumin has also been identified to suppress the proliferation, invasion, and metastasis of osteosarcoma (23,24,51,52).…”
Section: Inhibition Effect Of Curcumin On Tumorsmentioning
confidence: 99%
“…Overexpression of the EEF1A1 gene can specifically inhibit the TP53 gene [12], while TP53 is a well-known tumor suppressor gene. A study in 2018 proved that the EEF1A1 gene is involved in the occurrence of osteosarcoma through biological processes by constructing a PPI network and by GO analysis [13]. Figure 5B-5D shows that the EEF1A1 and YWHAZ genes were important genes in the network diagram of target genes.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies on whole-exome sequencing demonstrated that the TP53 and RB1 genes played a major role in recurrent changes in osteosarcoma (80-90% and 10-39%, respectively) [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. About 50% of patients with osteosarcoma have inactivating mutations in both the TP53 and RB1 genes.…”
Section: Discussionmentioning
confidence: 99%